PERSEPSI MAHASISWA AKUNTANSI STIE NASIONAL MENGENAI PENGARUH KUALITAS AKUNTAN, PEMANFAATAN TEKNOLOGI INFORMASI DAN SISTEM PENGENDALIAN INTERN TERHADAP KUALITAS LAPORAN KEUANGAN - Ferra Maryana; Bayu Indra Aditya (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2015)
Abstract, This study aimed to give empirical evidences about perceived of STIE Nasional accounting students in the effects of accountants qualities, usefull of information technology, and internal controls to the quality of financial statements. The dependend variable was quality of financial statements and the independent variables were accountants qualities, usefull of information technology, and internal controls. The population in this study was 287 accounting student of STIE Nasional in Banjarmasin. The data collected from the output of questionnaires which gived to the respondents. The samples technique used purposive sampling with 74 accounting students. The study gived empirical evidences that partially only usefull of information technology and internal controls which had effect on quality of financial statements but accountants qualities has no effect. It happened because even accountants have a good quality but they were not have good ethics so they can do some fraud, so the financial statements which product by them has no qualities. Simultaneously, all independent variables had effect on quality of financial statements.